Relationship between pharmacokinetics of fluazuron and its efficacy for controlling Rhipicephalus microplus: A comprehensive evaluation of tick drug uptake - Sarli, Macarena (2024)
Relationship between fluazuron (FZN) concentrations in cattle plasma and ticks and its therapeutic efficacy percentage (EP) against Rhipicephalus microplus was analyzed. The extent of FZN uptake by ticks after its topical administration was also evaluated. Heifers, naturally infested with R. microplus, were divided in treated and no treated groups. Blood and tick samples were taken to measure FZN concentrations and female ticks were counted to evaluate the EP of the treatment from day 0 to 45 post-treatment (PT). Ticks exposed (TE) and not exposed (TNE) to topical contact with the drug were collected at 12 and 24 h PT. Artificial feeding (AF) of ticks was also performed with blood from a treated heifer. The EP on days 21, 28, 35, 42 and 45 PT was 99.1, 92.3, 81.2, 74.7 and 76.5 %, respectively. Fluazuron disposition within ticks during the first 2 days post-treatment did not mirror the corresponding FZN levels in the bovine plasma, but a statistically significant positive correlation was evident from day 3. Mean FZN concentrations in TE at 12 h and 24 h PT were significantly higher than in TNE. The FZN concentrations in AF ticks were significantly lower than those in TE but comparable to the levels in TNE. The efficacy and pharmacokinetics analysis suggest that maintaining a threshold FZN plasma concentration above 20–25 ng/mL is crucial to prevent the development of larvae into engorged females. The results also indicate that direct absorption of FZN through the tick's integument occurs in the initial days after treatment.